Analyzing the transmitted and stored energy through multilayer protective fabric systems with various heat exposure time. Issue 3 (February 2016) - He, Jiazhen; Li, Jun
The energy transmitted directly during thermal exposure as well as the stored energy that is continuously discharged from the heated fabrics after exposure can contribute to burn injuries. This study examined the effect of heat exposure time on the transmitted and the stored energy through multilayer protective fabric systems. The influences of the exposure duration on the amount of transmitted energy, the amount of stored energy, and also the action period of the stored energy release were discussed. A newly developed index was introduced to evaluate the thermal protection levels. The analyses demonstrated that the amount of transmitted energy increased continuously with an increase of exposure time; however, the amount of stored energy released to the sensor was limited in the process of exposure time increase. The maximum amount of stored energy was about 14.0 J/cm 2 for the selected fabrics. As the exposure time was further increased the stored energy decreased to the range from 8.5 J/cm 2 to 13.7 J/cm 2 . The grade of the thermal protection against a second-degree burn injury decreased with the increase of the exposure duration. By using the introduced index, the thermal performance estimate values could be determined, thus avoiding use of the iterative techniques suggested by ASTM F2703.